Low risk of thyroid eye disease (TED) following radioiodine (RAI) therapy in a multidisciplinary setting: a retrospective cohort study - John S. Vekinis; Kirsty Clarke; Vickie Lee; Malik Moledina; Sairah R. Khan; Mitesh Naik; Karim Meeran (Thyroid Research)
Abstract Background Radioiodine (RAI) is recommended by the National Institute of Clinical Excellence (NICE) as a first-line definitive treatment of Grave’s hyperthyroidism (GH). RAI is cited as a major risk factor in the development and exacerbation of thyroid eye disease (TED). We aim to identify the current risk of TED in a population treated post 2015. Methods This is a retrospective cohort study including all adult patients diagnosed with GH undergoing RAI over a seven-year period. Data collected included age; gender; thyroid diagnosis and pre- and post-treatment thyroid status; length of GH; TSHR-Ab titres; smoking status; RAI dose and number of treatments; ophthalmology assessment and use of steroid prophylaxis. Investigation results, clinical scoring and management details were collected from patients who developed TED following RAI. Results Four of 231 patients (1.7%) treated with RAI over 8 years had new onset (two patients) or progression (two patients) of TED following their RAI. One required immunosuppression and one rehabilitative TED surgery. No patient developed sight-threatening TED. Conclusions In our study, judicious screening for high-risk patients and the use of prophylactic steroids results in lower rates of RAI associated TED relative to those reported previously in the literature.